How mathematics students perceive the transition from secondary to tertiary level with particular reference to proof - Furinghetti, Fulvia; Maggiani, Chiara; Morselli, Francesca (NOMAD Nordic Studies in Mathematics Education, 2012)
This paper reports on a research project concerning the difficulties met by undergraduate students in mathematics during the first year of university. Our aim is to provide elements for studying the transition from secondary to tertiary level as perceived by the students who live it. The combination of different analytical tools (questionnaires, interviews, problem solving and proving activities) allows shedding light on aspects which are not purely cognitive, but also pertain to the affective domain.